Dental medicine students’ knowledge of lateral cephalometric radiography in orthodontic treatment: a study at Mulawarman University - Subagio, Fania Triwidyanti; Agustin, Sylvia; Simbolon, Dame Rimmauli; Rokhim, Saiful; Cahya, Wahyuni Dwi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This research aims to evaluate some aspects of the knowledge level in dental medicine students at Mulawarman University regarding the use of lateral cephalometric radiography in orthodontic treatment. Materials and Methods: This research uses a quantitative methodology with a descriptive cross- sectional approach conducted at the medical faculty of the Mulawarman University dentistry study program located in Samarinda Ulu District. The research sample was taken by a total sampling method and consisted of 90 Mulawarman University dentistry students. Research data were obtained through primary data collection in the form of questionnaires that met the inclusion and exclusion criteria. Results: The results showed that more respondents had a good level of knowledge, with as many as 41 students (45.56%). The class of 2022 dental students had a more dominant level of good knowledge, with as many as 13 students (68.42%) of the total class of 2022 students, and the class of 2021 dental students also had a good level of knowledge, with as many as 13 students (59.09%) of the total class of 2021. The results also show that the factor of high interest in learning is owned by the class of 2022, as many as 18 students (94.74%), and high interest also affects knowledge, so that with high interest, you can get a good level of knowledge (97.56%). In addition, the factor of how to study by non-cramming learning method is dominantly owned by the class of 2022, as many as 15 students (78.95%), and the factor of how to study can affect one's knowledge, so that by learning not overnight, the speed system can get a good level of knowledge (78.05%). Conclusion: In general, dental medicine students are knowledgeable about lateral cephalometric radiography. This level of knowledge is good, and in this study, the results showed that the class of 2022 most dominantly exhibited a non-cramming method and a high level of learning interest.